Chromatin Ring Formation at Plant Centromeres - Schubert, Veit; Ruban, Alevtina; Houben, Andreas (Frontiers in Plant Science, 2016)
We observed the formation of chromatin ring structures at centromeres of somatic rye and Arabidopsis chromosomes. To test whether this behavior is present also in other plant species and tissues we analyzed Arabidopsis, rye, wheat, Aegilops and barley centromeres during cell divisions and in interphase nuclei by immunostaining and FISH. Furthermore, structured illumination microscopy (super-resolution) was applied to investigate the ultrastructure of centromere chromatin beyond the classical refraction limit of light. It became obvious, that a ring formation at centromeres may appear during mitosis, meiosis and in interphase nuclei in all species analyzed. However, varying centromere structures, as ring formations or globular organized chromatin fibers, were identified in different tissues of one and the same species. In addition, we found that a chromatin ring formation may also be caused by subtelomeric repeats in barley. Thus, we conclude that the formation of chromatin rings may appear in different plant species and tissues, but that it is not specific for centromere function. Based on our findings we established a model describing the ultrastructure of plant centromeres and discuss it in comparison to previous models proposed for animals and plants.